Collateral impact of the COVID−19 pandemic on the use of healthcare resources among people with disabilities - Sohn, Minjeong; Koo, Heejo; Choi, Heekyoung; Cho, Hyunsan; Han, Euna (Frontiers in Public Health, 2022)
Objective We assessed the collateral impact of the COVID-19 pandemic on healthcare service use among of people with disabilities. Methods We utilized the COVID-19 Database from the Korean Nnational Hhealth Iinsurance Service claims from 2015 through until June 2020. We included 5,850 people with disabilities and matched 5,850 without disabilitiesy, among those who were not neither tested nor diagnosed with COVID-19. We used a quasi-experimental setting with COVID-19 outbreak as an external event in a difference-difference estimation with matching controls. Results Subjects Participants with disabilities had recorded a larger drop decrease in the number of claims for total services (2.1 claims per 5 months) upon then COVID-19 pandemic’s onset than the non-disabledcompared to those without disabilities (1.6 claims), and the difference-in-differences estimates was were statistically significantly (0.46 claims). The decline was driven by outpatient and emergency visits. The extent of the decline was large for the severe disability group overall. By disability type, those with a physical disability showed a statistically significant decline in the number of claims. Conclusions There was collateral impact of The COVID-19 pandemic has had a collateral impact on healthcare use for people with disabilities’ use of healthcare services. Continued assessment is needed on regarding whether the collateral impact has been sustained or is following a different path is needed.